Transplanting Palms in the Landscape - Alan W. Meerow; Timothy K. Broschat (EDIS, 2009)
Revised! Circular 1047, a 9-page illustrated fact sheet by Timothy K. Broschat, discusses the various factors that contribute to palm transplant survival rate. Published by the UF Department of Environmental Horticulture, June 2009.